Validitas Buku Etnobotani Tumbuhan Nauclea subdita (Korth) Steud. di Kawasan Hutan Bukit Tamiang Kabupaten Tanah Laut - Sonia Audra; Dharmono Dharmono; Sri Amintarti (Program of Biology Education, Universitas Lambung Mangkurat, 2021)
Validation is an action taken to review the initial product, and then provides input for further improvement. This study aims to determine the validity of popular scientific books developed about the plant ethnobotany Nauclea subdita (Korth) Steud. in the Tamiang hill forest area of Tanah Laut Regency as teaching material in the form of popular scientific books. This research uses the development research method with the model of education design research (EDR) through formative evaluation of the tessmer test. The validation test was conducted by 2 expert validators. The results showed the popular scientific book Nauclea subdita (Korth) Steud. developed is classified as very valid, based on the results of expert validation which shows very valid criteria with a value of 90.63%.